Creative Thinking Ability Based on Self Efficacy on an Independent Learning Through Google Classroom Support - Dewi Mashitoh, Nur Livia; Sukestiyarno, YL.; Wardono, Wardono (Universitas Negeri Semarang, 2021)
Junior high school students need to be accustomed to thinking creatively. The 2015 TIMSS results show that the creative thinking ability of junior high school students still need to be optimized. This research aimed to discuss creative mathematical thinking ability based on sel efficacy on an independent learning through Google Classroom support. This research employed qualitative descriptive design. The population of this research was the students of class VIII. The subjects of the research were 6 students of class VIII selected based on three categories of self efficacy, they were: high, medium, and low. Two students were found in the high self-efficacy category, two students from the medium self-efficacy category and two students from the low self-efficacy category. The results of this research showed that students with high self-efficacy level were able to complete the four qualifications of creative thinking abilities, they were fluency, flexibility, originality, and elaboration. Students with the medium self-efficacy level were still having difficulty showing up ideas to determine the unusual way of being used. Students with low self-efficacy level had difficulty in understanding the problem so that it is only able to meet one qualification of creative thinking ability that is fluency. Based on the explanation of the results of this research, it can be concluded that no student with low self efficacy level has a high score of creative thinking ability